White matter microstructure in obesity and bipolar disorders: an ENIGMA bipolar disorder working group study in 2186 individuals - Dietze, Lorielle M F; McWhinney, Sean R; Favre, Pauline; Abé, Christoph; Alexander, Nina; Barkhau, Carlotta; Benedetti, Francesco; Berk, Michael; Bøen, Erlend; Boye, Birgitte; Brosch, Katharina; Canales-Rodríguez, Erick J; et al. (Molecular psychiatry, 2025)
Although specific risk factors for brain alterations in bipolar disorders (BD) are currently unknown, obesity impacts the brain and is highly prevalent in BD. Gray matter correlates of obesity in BD have been well documented, but we know much less about brain white matter abnormalities in people who have both obesity and BD. We obtained body mass index (BMI) and diffusion tensor imaging derived fractional anisotropy (FA) from 22 white matter tracts in 899 individuals with BD, and 1287 control individuals from 20 cohorts in the ENIGMA-BD working group. In a mega-analysis, we investigated the associations between BMI, diagnosis or medication and FA. Lower FA was associated with both BD and BMI in six white matter tracts, including the corpus callosum and thalamic radiation. Higher BMI or BD were uniquely associated with lower FA in three and six white matter tracts, respectively. People not receiving lithium treatment had a greater negative association between FA and BMI than people treated with lithium in the posterior thalamic radiation and sagittal stratum. In three tracts BMI accounted for 10.5 to 17% of the negative association between the number of medication classes other than lithium and FA. Both overweight/obesity and BD demonstrated lower FA in some of the same regions. People prescribed lithium had a weaker association between BMI and FA than people not on lithium. In contrast, greater weight contributed to the negative associations between medications and FA. Obesity may add to brain alterations in BD and may play a role in effects of medications on the brain.
Keywords: bílá hmota; Anisotropy; Male; šedá hmota; Obesity; Brain; obezita; Adult; dospělí; zobrazování difuzních tenzorů; mužské pohlaví; lidé; Gray Matter; Diffusion Tensor Imaging; ženské pohlaví; White Matter; anizotropie; Humans; Body Mass Index; mozek; index tělesné hmotnosti; Female; lidé středního věku; bipolární porucha; Middle Aged; Bipolar Disorder